If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 2(k + 2) Reorder the terms: 8 = 2(2 + k) 8 = (2 * 2 + k * 2) 8 = (4 + 2k) Solving 8 = 4 + 2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2k' to each side of the equation. 8 + -2k = 4 + 2k + -2k Combine like terms: 2k + -2k = 0 8 + -2k = 4 + 0 8 + -2k = 4 Add '-8' to each side of the equation. 8 + -8 + -2k = 4 + -8 Combine like terms: 8 + -8 = 0 0 + -2k = 4 + -8 -2k = 4 + -8 Combine like terms: 4 + -8 = -4 -2k = -4 Divide each side by '-2'. k = 2 Simplifying k = 2
| -9.1x=63.7 | | 6+6x=-4(6-3x) | | 3X^2+8X+XY-4Y=11 | | 1-4x=-7+28 | | (3x^2)+(8x)+(xy)-(4y)=11 | | (3x+8)+(2x+3)=180 | | 6(2x-3)=8x-2 | | 4(x-6)+6=6(x+2)-4 | | 0=-2x^2+4x+4 | | -c+3.4=6.21 | | -2.1m=8.4 | | 9-2x=7+2x-6 | | 10=2(y-4)+4 | | 56=c+24 | | -8(4b+3)+(33b-7)=0 | | 7x-9=3(x+5) | | 1.3x-2.39=5.67x+4.74 | | b+5=-10 | | .75a-.666=.583 | | 3(4-5k)-5(7-2k)+6=3k+7 | | .3333333334z-4=-.3333333334z+18 | | z^2+9z-9=(2z+3)(z-3) | | 2v^3-3v^2-14v+21=0 | | 6(x-3)=2x+4-6 | | 4-49v^2=0 | | -3/4+(-3/4)=0 | | -6x+16=-2x | | .5d=2-.5d | | 2/5+1/5=0 | | 4.8q-5.9-5.7q=-1.9q-4.2 | | 1.3p+0.3p-2=1.2 | | 15a^2+a=2 |